Comparative study of deliberate self harm in Tamils and Muslims in Batticaloa - Ganesan, M. (My University, 2003)
More people have died of suicide than the ongoing ethnic war in the last fifteen years (2). The real suicide figures are likely to be much higher. The reasons for the high suicide rate are not very clear. Agrochemical poisoning is reported as the most common method in the country; followed by poisonous seeds, hanging, jumping in front of trains, and drowning. Self immolation is generally thought to be less common (2,3). The suicide rates started to increase steeply after the sixties (4) and peaked around mid eighties (3), since then it has been fairly static around this level. Suicide in the Tamil community in the north of the country has been studied to some extent (3,5). Suicide rate among the Tamils was high before the war at 33.3 (7). The suicide rate in northern Sri Lanka then shows a dramatic decrease with the onset of the war. Some risk factors or themes appear to have similar influence among the Tamils and Muslims with regards to deliberate self-harm. Aggression within families, previous attempts, deliberate self-harm in family, family conflicts, social isolation were the themes that recurred in both communities to the same extent. However, from the above results significant differences in the risk factors for deliberate self- harm between the two communities too become apparent. Shame, Family conflicts, and anger are themes that recur in the histories of the Tamil patients. On the other hand, in the Muslim patients these did not come up as important risk factors. Among Muslims the common themes were major psychiatric illness and early loss of a parent. This indicates the Tamils and Muslims appear to be two different populations with regards to risk factors for deliberate self-harm. Alcohol seems to have a big influence in the generally dry Muslim community as a risk factor to deliberate self-harm. This is in keeping with literature from elsewhere. This study also shows the risk factors for deliberate self-harm inc1u~e local cultural factors in addition to the more global risk factors such as mental illness. In some communities, these local cultural factors play an important role and in other communities, they are less significant. In societies living close to each other, significant differences in the risk factors for deliberate self-harm are possible. This type of comparison using qualitative methods is a useful exercise to tease out these differences between communities. This will help to develop preventive programs targeting specific communities. Here too, these two communities in spite of living close to each for a long time seem to have important differences with regards to self-harm. In spite of some global factors local factors too appear to be important in the decision to self-harm